Perubahan Pandangan Masyarakat Terkait Pentingnya Pendidikan Anak Usia Dini Di Desa Cimerak - Erni Triana Agustin; Nurina Fadilatu Shaumi; Uminah Shaumi (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
This research aims to find out how people's views have changed regarding the importance of early childhood education in Cimerak Village. The method in this research uses a case study method with a qualitative approach where researchers go directly to the field to uncover problems according to the research focus. The research results show that after the establishment of the PAUD institution in Cimerak Village, many parents started sending their children to pre-school institutions. This is one of the responses from the community which supports the establishment of pre-school educational institutions at the village level. After the establishment of the PAUD institution in the local village, parents felt that many positive changes had occurred in their children, such as: increasing self-confidence, increasing creativity and developing children's social skills.